High efficiency and clean separation of eucalyptus components by glycolic acid pretreatment. (December 2021) - Luo, Yadan; Li, Yan; Cao, Liming; Zhu, Jiatian; Deng, Baojuan; Hou, Yajun; Liang, Chen; Huang, Caoxing; Qin, Chengrong; Yao, Shuangquan
Graphical abstract: Highlights: A new green solvent system, glycolic acid pretreatment, has been discovered. The separation of hemicellulose was highly selective. The depolymerization and repolymerization of lignin were inhibited. The separation rate of hemicellulose was as high as 65.08%. The recovery rate of glycolic acid was as high as 91%. Abstract: Glycolic acid has chemical properties similar to those of formic acid. Therefore, similar to formic acid pretreatment, glycolic acid pretreatment has the separation effect of hemicellulose. In this study, eucalyptus hemicellulose was effectively separated by glycolic acid pretreatment. The effects of glycolic acid concentration, temperature and time on the separation of cellulose, hemicellulose and lignin were investigated. The optimum conditions were acid concentration 5.40%, temperature 140 °C, time 3.0 h. The highest yield of xylose was 56.72%. The recovery rate of glycolic acid was 91%. Compared to formic acid, the yield of xylose increased to 10.33% while that of lignin decreased to 11.08%. It showed high selectivity for hemicellulose separation, yielding 65.48% hemicellulose with 72.08% purity. The depolymerization and repolymerization of lignin were inhibited. The integrity of the cellulose structure was preserved. It provides theoretical support for the fractional separation and high-value transformation of lignocellulosic biomass.